From Read-Aloud Practice to Interactive Storytelling: Teachers’ Strategies for Using Storybooks in Early Childhood Learning at Tadika Alfikh Orchadch - Niko Alek Sidabutar; Zuliana Zuliana (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2026)
Storybooks are widely used in early childhood education to support language stimulation, children’s engagement, and the introduction of simple moral values. However, classroom practice often remains limited to one-way read-aloud activities, leaving children with few opportunities to respond, interpret, and participate actively in storytelling. This study examines teachers’ strategies for using storybooks interactively with young children at Tadika Alfikh Orchadch, identifies the obstacles teachers face, and describes the efforts made by teachers and the institution to improve storytelling activities. The study employed a descriptive qualitative approach. Data were collected through classroom observations, teacher interviews, and learning documentation involving six teachers and one class of ten children aged four to five years. The data were analyzed through data reduction, data display, and conclusion drawing, while trustworthiness was strengthened through technique triangulation. The findings indicate that teachers used storybooks mainly through read-aloud activities, picture display, voice intonation, simple questioning, and connections between story content and children’s daily experiences. However, more participatory activities, such as character discussion, role-play, drawing, and story retelling, were not implemented consistently. The main obstacles included limited teacher skills in designing follow-up activities, children’s short attention span, limited classroom time, and insufficient variety of storybooks. Teachers and the institution had made initial efforts to improve storytelling through expressive reading, experience-based questioning, classroom media, and support for storybook use, but these efforts still required stronger pedagogical and institutional support. This study concludes that storybooks can create opportunities for language stimulation and the introduction of simple moral values when teachers transform read-aloud practice into more dialogic and participatory storytelling.